Supporting poverty reduction in low-income developing countries : the international community's response - Ahmed, Masood (2000)
Focuses on efforts being made by the World Bank, IMF and UN agencies in poverty alleviation. Highlights work that is being done in 30 low-income countries with poverty reduction strategy papers.